Phase II Trial of Erlotinib during and after Radiotherapy in Children with Newly Diagnosed High-Grade Gliomas - Qaddoumi, Ibrahim; Kocak, Mehmet; Pai-Panandiker, Atmaram S.; Armstrong, Gregory T.; Wetmore, Cynthia; Crawford, John R.; Lin, Tong; Boyett, James M.; Kun, Larry E.; Boop, Fredrick A.; Merchant, Thomas E.; Ellison, David W.; et al. (Frontiers in Oncology, 2014)
Background: Epidermal growth factor receptor is overexpressed in most pediatric high-grade gliomas (HGG). Since erlotinib had shown activity in adults with HGG, we conducted a phase II trial of erlotinib and local radiotherapy (RT) in children with newly diagnosed HGG. Methods: Following maximum surgical resection, patients between 3 and 21 years with non-metastatic HGG received local RT at 59.4 Gy (54 Gy for spinal tumors and those with ≥70% brain involvement). Erlotinib started on day 1 of RT (120 mg/m2 per day) and continued for 2 years unless there was tumor progression or intolerable toxicities. The 2-year progression-free survival (PFS) was estimated for patients with intracranial anaplastic astrocytoma (AA) and glioblastoma (GBM). Results: Median age at diagnosis for 41 patients with intracranial tumors (21 with GBM and 20 with AA) was 10.9 years (range, 3.3–19 years). The 2-year PFS for patients with AA and GBM was 15 ± 7 and 19 ± 8%, respectively. Only five patients remained alive without tumor progression. Twenty-six patients had at least one grade 3 or 4 toxicity irrespective of association with erlotinib; only four required dose modifications. The main toxicities were gastrointestinal (n = 11), dermatologic (n = 5), and metabolic (n = 4). One patient with gliomatosis cerebri who required prolonged corticosteroids died of septic shock associated with pancreatitis. Conclusion: Although therapy with erlotinib was mostly well-tolerated, it did not change the poor outcome of our patients. Our results showed that erlotinib is not a promising medication in the treatment of children with intracranial AA and GBM.